Cystic fibrosis and the clinical biofilm revolution A survey of the Danish CF Center's contribution - Niels Høiby (Biofilm)
Background: Biofilm infections are chronic infections which are difficult to diagnose. Biofilm infections are tolerant to antibiotics and the defense mechanisms of the host. Patients with the genetic disease cystic fibrosis (CF) produce viscid mucus in the respiratory tract and therefore suffer from chronic biofilm infections in their lungs and paranasal sinuses.The most important microorganism is the mucoid phenotype of Pseudomonas aeruginosa which causes chronic biofilm infections in the lungs of CF patients and untreated patients succumb as children if they contact this biofilm infection.Since CF patients are treated in CF Centers all over the world, it is possible to do longitudinal studies on epidemiology, pathophysiology, diagnosis, prevention and treatment of P. aeruginosa biofilm infection which is not possible if such patients are not followed in specialized centers.This survey describes the research through several decades in the Danish CF Center in Copenhagen which have changed the epidemiology, treatment, prophylaxis and prognosis of CF patients worldwide. Based on these results ESCMID Guidelines for diagnosis and treatment of biofilm infections were published which have influenced biofilm research and treatment in other areas.